Adoption Gaps of Environmental Adaptation Technologies with Public Effects - Angelo Antoci; Simone Borghesi; Giulio Galdi; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2019)
The global nature of the climatic challenge requires a high level of cooperation among agents, especially since most of the related coping strategies produce some kind of externalities toward others. Whether they are positive or negative, the presence of externalities may lead the system towards Pareto-dominated states. In this work, we study under and over-adoption of environmental adaptation technologies which enhance environmental quality for the individual while transferring externalities to other agents. We distinguish adaptation technologies between maladaptation and mitigation ones, depending on the sign of the externalities. In particular, we show that over adoption may occur for maladaptive technologies, whereas under-adoption may occur in case of mitigation. We study a model with two regions at different stages of development, which allows us to draw considerations on well-being consequences of environmental dumping.
Keywords: C70; D62; O13; O40; Q20; 330; Adaptation; Negative Externalities; Evolutionary Dynamics; Public Good Game; Environmental Dumping